Security and Privacy in Communication Networks 5th International ICST Conference, SecureComm 2009, Athens, Greece, September 14-18, 2009, Revised Selected Papers - Chen, Yan; Dimitriou, Tassos D.; Zhou, Jianying (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2009)
This book constitutes the thoroughly refereed post-conference proceedings of the 5th International ICST Conference, SecureComm 2009, held in September 2009 in Athens, Greece. The 19 revised full papers and 7 revised short papers were carefully reviewed and selected from 76 submissions. The papers cover various topics such as wireless network security, network intrusion detection, security and privacy for the general internet, malware and misbehavior, sensor networks, key management, credentials and authentications, as well as secure multicast and emerging technologies.